Early life environment affects behavior, welfare, gut microbiome composition, and diversity in broiler chickens - de Jong, Ingrid C.; Schokker, Dirkjan; Gunnink, Henk; van Wijhe, Maudia; Rebel, Johanna M. J. (Frontiers in Veterinary Science, 2022)
This study aimed to identify whether early-life conditions in broiler chickens could affect behavior and welfare, and whether or not this was associated with an altered gut microbiome composition or diversity. Broilers were tested in a 2x2 factorial design with hatching conditions (home pen (OH) or at the hatchery (HH)) and enrichment (dark brooder (EE) or no brooder (NE) until 14 days of age) as factors (N=6 per treatment combination). Microbiota composition was measured in the jejunum at day (d) 7, 14 and 35 and in pooled faecal samples at d14. A novel environment test (NET) was performed at d1 and 11 and behavior was observed at d6, 13 and 33. At d35, composite asymmetry was determined, and footpad dermatitis and hock burn were scored. In their home pen, HH showed more locomotion than OH (P=0.05) and NE were sitting more and showed more comfort behavior than EE at all ages (P<0.001 and P=0.001 respectively). At d6 and 13 NE showed more eating and litter pecking while sitting, but at d33 the opposite was found (age*enrichment: P=0.05 and P<0.01, respectively). At d1 and 11, HH showed more social reinstatement in the NET than OH, and EE showed more social reinstatement than NE (P<0.05). Composite asymmetry scores were lower for EE than NE (P<0.05). EE also had less footpad dermatitis and hock burn than NE (P<0.001). Within OH, NE had a more diverse faecal and jejunal microbiome compared to EE at d14 (faeces: observed richness: P=0.052; jejunum: observed richness and Shannon: P<0.05); principle component analysis (PCA) showed differences between NE and EE within both HH and OH in faecal samples at d14, as well as significant differences in bacterial genera such as Lactobacillus and Lachnospiraceae (P<0.05). At d 35, PCA in jejunal samples only showed a trend (P=0.068) for differences between NE vs EE within OH. In conclusion, these results suggest that especially the dark brooder affected the behavior and had a positive effect on welfare, and affected both microbiome composition and diversity. Whether or not the behavior was modulated by the microbiome, or vice versa, remains to be investigated.